Transdermal delivery of colchicine using dissolvable microneedle arrays for the treatment of acute gout in a rat model - Yang Liu; Xiaoruo Zhu; Shiliang Ji; Zhen Huang; Yuhui Zang; Ying Ding; Junfeng Zhang; Zhi Ding (Taylor & Francis Group, 2022)
Colchicine (Col) is used to prevent and treat acute gout flare; however, its therapeutic use is strictly limited owing to severe gastrointestinal side effects after oral administration. Therefore, we developed a dissolvable Col-loaded microneedle (MN) with hyaluronic acid to deliver Col via the transdermal route. We studied the preparation, mechanical properties, skin insertion, skin irritation, drug content, and transdermal release of the Col-loaded MN. The pharmacokinetics of Col after Col-loaded MN application were compared with those of Col solution gavage over 24 h. Knee joint edema evaluation and the hindfoot mechanical threshold test were conducted to determine the pharmacodynamic profile. The dissolvable Col-loaded MN possessed sufficient mechanical strength to penetrate the skin and release the loaded drug. No skin irritation was observed for 3 days after application. We found that 3.36-fold more Col contained in MNs was delivered through the skin compared with that in gel in vitro, and moderate relative bioavailability in vivo. The Col-loaded MN significantly relieved swollen knee joints and mechanical hypernociception in an acute gout model in rats. The dissolvable Col-loaded MN array reduced inflammation and pain via topical administration when acute gout occurred. Reducing the gastrointestinal side effects of Col-loaded MNs is expected to optimize the therapeutic effects of Col and improve patient compliance.